2011
DOI: 10.1108/13620431111107793
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting work commitment: the role of Machiavellianism

Abstract: PurposeThe aim of this paper is to refine the concept of work commitment by proposing a dissociation between self‐related work commitment (namely, employees' career commitment) and other‐related work commitment (pertaining more strongly to others such as team members or supervisors). The dissociation is demonstrated empirically through the differential predictive validity of Machiavellianism, which holds when the influence of broad personality dimensions is controlled for.Design/methodology/approachPersonality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 69 publications
7
71
0
11
Order By: Relevance
“…For instance, it has been found that narcissistic individuals are more likely to emerge as leaders and are also perceived to be more effective as leaders (Brunell et al, 2008;Nevicka, Ten Velden et al, 2011), that psychopathy in managers is positively associated with ratings of charisma and presentation style (Babiak, Neumann, & Hare, 2010), and that Machiavellianism in employees is positively related to career commitment (Zettler, Friedrich, & Hilbir, 2010). These findings suggest that having these traits may be helpful in securing a successful career, and that-in the business context-it may pay off to confidently strive for one's own personal goals with little or no regard for others.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, it has been found that narcissistic individuals are more likely to emerge as leaders and are also perceived to be more effective as leaders (Brunell et al, 2008;Nevicka, Ten Velden et al, 2011), that psychopathy in managers is positively associated with ratings of charisma and presentation style (Babiak, Neumann, & Hare, 2010), and that Machiavellianism in employees is positively related to career commitment (Zettler, Friedrich, & Hilbir, 2010). These findings suggest that having these traits may be helpful in securing a successful career, and that-in the business context-it may pay off to confidently strive for one's own personal goals with little or no regard for others.…”
Section: Introductionmentioning
confidence: 95%
“…Recent researches have now focused on so-called "successful" psychopaths and narcissists in some context [6], and the dark triad embodies a few of desirable traits like charm, assertiveness, and impression management skills [12]. However, numerous studies have articulated that narcissism has been linked to unethical behavior in CEOs and a need for power [13][14][15], psychopaths can adversely affect productivity [13], and Machiavellianism is associated with diminished organizational commitment [16,17], with a tendency to focus on power and manipulative behaviors [13,18].…”
Section: The Negative Traitmentioning
confidence: 99%
“…occupational commitment (Blau, 2006;Cohen 2007)), kaip įsiparei-gojimas karjerai (angl. career commitment (Zettler et al, 2011)), kaip karjeros įtvir-tinimas (angl. career entrenchment (Carson et al, 1996)).…”
Section: įVadasunclassified